"I wouldn't want anything that would change who he is." The relationship between perceptions of identity and attitudes towards hypothetical gene-editing in parents of children with autosomal aneuploidies - Kathryn Elliott; Nivedita Ahlawat; Erika S. Beckman; Kelly E. Ormond (Elsevier, 2022)
Attitudes towards hypothetical somatic and germline gene-editing technologies for those who are directly impacted by genetic conditions are of increasing importance as these potential therapeutics are developed. This study is a secondary analysis of 27 semi-structured interviews conducted with parents of children with Trisomy 13 (N ​= ​9), Trisomy 18 (N ​= ​8), or Trisomy 21 (N ​= ​10) that aimed to explore the relationship between perceptions of identity as it relates to the trisomy within the family and parental attitudes towards gene-editing. A codebook was developed using both deductive and inductive approaches. All transcripts were coded and every third was adjudicated to consensus. Identity themes that emerged were integrated into a framework that conceptualized the relationship between participants' perceptions of identity and their attitudes towards somatic and germline gene-editing. Participants varied in the degree to which they incorporated their child's trisomy into their perception of their child's identity (from a series of medical features to "who the child is") and their identity as a parent (from a barrier to expected adult and parenting experiences to a catalyst for personal, parental, and social change). Participants who viewed the trisomy as separate from identity were more likely to favor gene-editing as a restorative therapy, while participants who conceptualized their child's trisomy as fundamental to identity were more likely to oppose gene-editing as an unwelcome cure. Participants who had discrepant views about the incorporation of the trisomy into their child's identity and their own identity had more complex attitudes towards gene-editing. Considering perceptions of identity as it relates to genetic conditions and its role in attitudes towards potential therapeutics is important for researchers, policy makers, and practitioners who will develop, regulate, and implement gene-editing technologies.